Hubungan Efikasi Diri dan Kedisiplinan Belajar dalam Pembelajaran Pendidikan Pancasila pada Siswa SD di Kelurahan Lubang Buaya - Talitha Cahyawati Estiningtyas; Prayuningtyas Angger Wardhani; Nina Nurhasanah (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the relationship between self-efficacy and learning discipline in Pancasila education among fifth-grade elementary school students in the Lubang Buaya sub-district. Methods – This study employed a quantitative approach with a correlational design. The population consisted of 703 fifth-grade students from 11 public elementary schools in Lubang Buaya Subdistrict. A sample of 255 students was selected proportional sampling technique. Data was collected using a self-administered questionnaire to measure self-efficacy and academic discipline in Pancasila Education classes. The data were analyzed using Pearson’s product-moment correlation test with the assistance of IBM SPSS Statistics, after meeting the requirements for normality and linearity. Findings – The findings indicate a positive and significant relationship between self-efficacy and learning discipline in Pancasila Education among fifth-grade elementary school students. This is demonstrated by a correlation value of r = 0.551 and a significance test with a calculated t-value of 10.515. These findings indicate a positive and significant relationship with moderate strength. self-efficacy explains 30.4% of the variance in learning discipline and 69.6% influenced by other factors.Research Implications – The findings of this study highlight the importance of focusing on strengthening students’ self-efficacy as one of the factors related to their academic discipline in Pancasila Education classes. The limitations of this study include its inability to demonstrate a cause-and-effect relationship, as well as the fact that the population was limited to the Lubang Buaya subdistrict. Future research is recommended to expand the study population and examine other factors, either using the same research design or a different one.